Inclusive education in Chad: in-service teachers’ perceptions, practices, challenges, and expectations - Djekourmane, Denis; Huang, Xinyi; Xu, Tian (Frontiers in Education, 2026)
ObjectivesScholars have increasingly focused on inclusive education as a critical approach for addressing educational inequalities and fostering equitable participation for all learners. The purpose of this study is to examine in-service teachers’ perceptions, practices, challenges, and expectations regarding inclusive education in Chad, a sub-Saharan African country where limited research exists on this topic. Grounded in the inclusive pedagogy framework, the study explores how teachers understand educational exclusion and inclusion and how they respond to the diverse socio-economic, political, cultural, linguistic, and religious backgrounds of their students.MethodsA qualitative research approach with phenomenological design was employed using semi-structured, open-ended interviews with 23 in-service teachers (6 female and 17 male teachers). Data were analyzed through thematic analysis to identify patterns in teachers’ perceptions and practices related to inclusive education.FindingsFour major themes emerged from the research findings: (1) teachers’ perceptions of exclusion, (2) understanding of inclusion, (3) inclusive teaching practices, and (4) challenges in implementation. Specifically, teachers identified exclusion based on religion, ethnicity, political affiliation, economic status, and geographic origin, yet tended to overlook gender, disability, and refugee status. Further, while some inclusive practices—such as resource sharing, recognizing individual needs, facilitating group work, and maintaining neutrality were evident, teachers rarely addressed students’ emotional or psychological well-being. Key challenges included insufficient pre-service and in-service training, limited systemic and institutional support, and reluctance to engage with socially and politically sensitive issues, which may unintentionally sustain social inequalities.Discussion and conclusionIn-service teachers expressed a strong need for more practical guidance and clearer policy frameworks to support inclusive teaching. The findings highlight the importance of reforming teacher education to integrate inclusive pedagogy, multicultural content, social justice principles, and reflective practice. Strengthening teacher agency and providing structured support systems are crucial for fostering equitable and supportive learning environments. The study concludes by outlining theoretical and practical implications and suggesting future research directions, including studies using mixed or combined methods.